Review of Corrine Lennox and Matthew Waites (eds), Human Rights, Sexual Orientation and Gender Identity in The Commonwealth: Struggles for Decriminalisation and Change (Institute of Commonwealth Studies, London, 2013) - Hamzić, Vanja (Oxford University Press, 2014)
One important conclusion that the two co-editors make in a fairly straightforward manner is that they are ultimately sceptical of whether the Commonwealth, as an intergovernmental organisation, could play a positive role in the future (p. 538). ‘Here we can only acknowledge the tensions and help open up, rather than resolve, necessary debates’, write Lennox and Waites, ‘over the extent to which the Commonwealth can be reinvented through human rights’ (p. 544). And, this is, perhaps, of crucial importance. It will arguably take much more than the Commonwealth’s formal commitment to human rights relating to sexual orientation and gender identity to undo this organisation’s burdensome colonial legacy, including in the processes of criminalisation and decriminalisation of same-sex sexual behaviour. Lennox and Waites are right to conclude that ‘it is voices of the South that will carry the greatest legitimacy in eradicating a harmful colonial legacy’ (p. 544); but, such voices are incomplete and less effective without ‘Southern epistemologies [and] theories’ (p. 13), which, although promised, do not feature prominently in the volume. Still, one cannot deny that a pioneering trail has been blazed by this book, which invites future travellers to more daring and comprehensive undertakings.